Influence of Ce on Microstructure and Properties of High-carbon High-boron Steel. Issue 6 (June 2015) - Yong, Xiang; Zhiguo, Chen; Xiang, Wei; Zhongjia, Wu
Abstract The influence of Ce on the microstructure and the properties of high-carbon high-boron steel (HCHBS) were investigated by optical microscopy (OM), scanning electronic microscopy (SEM), and X-ray diffraction (XRD). The results indicate that the impact toughness and the wear resistance of the HCHBS can be significantly enhanced by adding of Ce, whereas the addition of Ce has no obvious effect on hardness. After being modified by Ce, the primary austenite grains of the HBHBS are greatly refined and most of the fishbone-like and lamellar borocarbides transform into blocky and granular borocarbides; meanwhile, the distribution of borocarbides becomes more uniform.